2006
DOI: 10.1161/circulationaha.105.585703
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Arterial Wall Remodeling During Lipid-Lowering Therapy

Abstract: Constrictive remodeling of the arterial wall was observed during plaque-stabilizing therapy with statin medications and appears related to their antiinflammatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(38 citation statements)
references
References 36 publications
6
28
0
4
Order By: Relevance
“…Our observations extend those of Nicholls et al [3] and differ from earlier, smaller studies that failed to demonstrate a relationship between HbA 1c and remodelling [11,20]. In the Reversal of atherosclerosis with aggressive lipid lowering therapy (REVERSAL) trial, a similarly sized trial to our own, diabetes status was not a predictor of coronary artery remodelling, but data on FBG and HbA 1c were lacking [10].…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Our observations extend those of Nicholls et al [3] and differ from earlier, smaller studies that failed to demonstrate a relationship between HbA 1c and remodelling [11,20]. In the Reversal of atherosclerosis with aggressive lipid lowering therapy (REVERSAL) trial, a similarly sized trial to our own, diabetes status was not a predictor of coronary artery remodelling, but data on FBG and HbA 1c were lacking [10].…”
Section: Discussionsupporting
confidence: 51%
“…To date, most imaging studies relating glycaemic status to CAD have lacked information on serial examinations [2,11,12,19,20], diabetes treatment [3,5,[10][11][12]19], FBG [5,10,11,19,20] or a non-diabetic control group [11,20]. Our investigation provides more detailed information than these previous reports, helps clarify some of the outstanding questions on this subject and complements the results from a recent pooled analysis of five randomised clinical trials [3].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Serial IVUS studies confirmed that remodeling is an important process during disease progression/regression. These studies demonstrate that plaque-stabilizing therapy is associated with constrictive remodeling 124 .…”
Section: Correlation Between Ivus and Cimtmentioning
confidence: 69%